Penggunaan lingkungan sekolah sebagai laboratorium IPA untuk meningkatkan aktivitas pembelajaran keanekaragaman hayati kelas VII SMP - Hasanah, Uswatun; Ani Nikmah; Rizqi Nur Rachmawati; Fitri Rizkiyah; Mona Anju Sansena (Universitas Garut, 2024)
This research aims to examine the effectiveness of utilizing the school environment as an IPA (Science) laboratory to enhance Science learning activities, specifically on biodiversity material, by comparing an experimental class and a control class involving seventh-grade students at SMP Penerus Bangsa, Tangerang City. The background of the problem indicates that conventional learning of biodiversity often triggers less active student engagement and a superficial understanding. Therefore, an approach that leverages existing natural resources around the school is considered to have the potential to overcome this problem. The research method used is a quantitative method with a quasi-experimental design involving two groups: an experimental group that learned using the school environment as an IPA laboratory and a control group that used conventional methods in the classroom. The learning sample was conducted through direct investigation, observation, identification, and classification of organisms in various school habitats (e.g., gardens, yards, and grassy areas). Data collection on learning activities was carried out through observation sheets and response questionnaires